Cryptococcal meningitis associated with interleukin‐17 inhibitor use for psoriasis. Issue 8 (8th June 2022) - Driver, Joseph; Zaayman, Marcus; Silfvast‐Kaiser, Annika; Menter, Alan
Abstract: Invasive fungal infection is a rare but serious potential consequence of biologic therapy. Herein, we report a case of cryptococcal meningitis in an otherwise immunocompetent patient receiving ixekizumab for the treatment of severe plaque psoriasis. We also discuss the relevant immunologic role of interleukin‐17, the potential for synergistic effects when transitioning biologic therapies, and clinical considerations when treating patients with such medications. To the best of our knowledge, this is the first case of cryptococcal meningitis reported in a patient treated with ixekizumab.